Synthesis and Biological Evaluation of N-Alkyl-3-(alkylamino)-pyrazine-2-carboxamides - Semelkova, Lucia; Konecna, Klara; Paterova, Pavla; Kubicek, Vladimir; Kunes, Jiri; Novakova, Lucie; Marek, Jan; Naesens, Lieve; Pesko, Matus; Kralova, Katarina; Dolezal, Martin; Zitko, Jan (Molecules (Basel, Switzerland), 2015)
A series of N-alkyl-3-(alkylamino)pyrazine-2-carboxamides and their N-alkyl-3-chloropyrazine-2-carboxamide precursors were prepared. All compounds were characterized by analytical methods and tested for antimicrobial and antiviral activity. The antimycobacterial MIC values against Mycobacterium tuberculosis H37Rv of the most effective compounds, 3-(hexylamino)-, 3-(heptylamino)- and 3-(octylamino)-N-methyl-pyrazine-2-carboxamides 14‒16, was 25 μg/mL. The compounds inhibited photosystem 2 photosynthetic electron transport (PET) in spinach chloroplasts. This activity was strongly connected with the lipophilicity of the compounds. For effective PET inhibition longer alkyl chains in the 3-(alkylamino) substituent in the N-alkyl-3-(alkylamino)pyrazine-2-carboxamide molecule were more favourable than two shorter alkyl chains.
Keywords: Fatty Acid Synthases; Spinacia oleracea; pyrazine; Electron Transport; aminodehalogenation; Pyrazines; alkylation; pyrazinamid; Mycobacterium tuberculosis; pyrazinamide; structure-activity relationships; chloroplasty; Microbial Sensitivity Tests; transport elektronů; Bacterial Proteins; Antitubercular Agents; Pyrazinamide; vztahy mezi strukturou a aktivitou; inhibition of photosynthetic electron transport; syntázy mastných kyselin; mikrobiální testy citlivosti; antimycobacterial activity; bakteriální proteiny; pyraziny; Structure-Activity Relationship; antituberkulotika; Chloroplasts